Daya Tarik Media Digital sebagai Media Dakwah untuk Generasi Milenial - Erwan Efendi; Maulana Adzi Fatin; Nur Fadilla Sari (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Technological developments in this day and age increasingly influence the model of da'wahprogress and develop rapidly. One of the technological trends in this millennial era is digital media because it is faster and easier to get information. Technology influences people's lives today, especially with the rise of global culture and instant lifestyles. Technological developments have also influenced the model of da'wah which fosters morals among the millennial generation along with the process of searching for their identity. Da'wah is calling, calling, inviting and encouraging someone to do good things. Da'wah must be able to take advantage of the situation well and as fully as possible. If not, then da'wah will lag behind and slow down, thereby affecting the morals and morals of the millennial generation. This article discusses whether digital media can attract the millennial generation in preaching. Using the literature study approach method, the data was then analyzed descriptively, explaining that da'wah through digital da'wah, such as using social media as a trendy and current communication medium, can become an attraction for millennials to always preach. This is because many people use social media as a medium in an effort to convey da'wah messages.